PERILAKU KONSUMSI MASYARAKAT KELAS MENENGAH DI KECAMATAN CURUG TANGERANG PADA MASA PANDEMI COVID-19 - Panggabean, Gabriela Dona Insani; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
The existence of a middle class society in Indonesia is difficult to identify and is a driving force for a country's economy due to the nature of consumption which tends to be high. During the Covid-19 Pandemic it had an impact on society, one of which was the economic impact. Curug District is a strategic area and has a high heterogeneity of population. This study uses qualitative research methods and is analyzed using the theory of the leisure class or the spendthrift class initiated by Thorstein Veblen. The formulation of the problem from this research is how the impact of the Covid-19 Pandemic has on middle-class people in Curug District and how is the consumption behavior of middle-class people during the Covid-19 Pandemic in Curug District. The results of this study are middle class people during the Covid-19 Pandemic in Curug Tangerang District tend to be excessive. There is an impact on consumption behavior patterns as a leisure class, namely the attention in using cultural industry products that have symbols in order to gain recognition from the community. Declining income is not an obstacle to excessive consumption. The use of loan services and credit payment methods is a strategy for fulfilling consumption instincts during a downturn in economic conditions during the Covid-19 Pandemic. This is in line with Veblen's theory which suggests the nature of the leisure class which uses predatory instincts to channel excessive consumption instincts. The advice obtained from this research is for middle class people not to develop excessive consumption behavior and adapt their lifestyle to their income, for the government to make this research a reference in making decisions related to development planning in the development of Curug District in the social and economic sectors. Keywords: consumption behavior, middle class, Covid-19 pandemic